Fintech and the Economic Crisis Caused by COVID-19 - Amaya Medina, Will Yhonatan; Moreno Sánchez, Deisy; Nova Rodríguez , Vladimir (Universidad Pedagógica y Tecnológica de Colombia, 2023)
This paper aims to analyze the opportunities of fintech in the face of the economic crisis generated by COVID-19, which has had a great impact on companies and on the lives of people who have been forced to reinvent their work, consumption habits and their interaction with the environment in order to sustain themselves in an increasingly competitive market that affect their lifestyle. It is essential to bear in mind that the traditional system and the government have made efforts to maintain the country's economic stability, but the results have not been very satisfactory. Therefore, a triangular-type exploratory research is carried out from the qualitative and quantitative aspects, through the application of information collection instruments, identifying financial, organizational and strategic of the SMEs in the city of Bogotá, that reported their financial statements with cutoff to December 2021 to the Superintendency of Corporations. Finally, it is evident the opportunity for fintech to do disruptive technological innovation for the development of financial products through connectivity from mobile devices for personal use that allow monitoring, electronic commerce, transaction systems, financing, decision-making models and optimization of financial processes at a low cost, which makes it possible to open a range of multiple opportunities for SMEs that seek greater participation and competitiveness where they can offer their products and services in an efficient, agile, comfortable and reliable way.